Does the blood glucose control have an effect on the success of the painful diabetic neuropathy treatment? - Jovanikic, Olivera; Andjelić, Gordana; Lepić, Milan; Mirković, Dušica; Jovanović, Bojan; Lepić, Toplica; Dragović, Tamara (Vojnosanitetski pregled, 2020)
Background/Aim. Diabetic neuropathy (DN) is the basic complication of diabetes, associated with impared glucoregulation, metabolic distrurbances, microvascular vessel damage and increased cardiovascular risk. We monitored the impact of glucoregulation on the efficacy of painful diabetic neuropathy (PDN) treatment, when all pharmaceutical treatment options were exhausted. Methods. Patients (n = 53, both gender, average age 68.3 ± 12.6) with PDN resistant to the pharmacotherapy were treated with the ultrasound-guided local anesthetic (0.5% procaine hydrochloride, 1% lidocaine, 0.25% levobupivacaine) blocks. Neuropathy was confirmed in accordance with the applicable European Federation of Neurological Societies (EFNS) criteria. Glycosylated hemoglobin (HbA1C) and blood glucose levels were monitored before and after therapy and one month after the treatment. Neuropathic pain was confirmed by Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) or Douleur neuropathique (DN4) or pain DETECT scales. The pain intensity was assessed by Visual analog scale, Neuropathic pain symptom and Neuropathic pain symptom inventory (VAS, NPS and NPSI, respectively) scales before and after therapy and one month after the treatment. The efficacy of the therapy was assessed as: excellent result (> 50% of pain loss), good result (30%–49% of pain loss and the therapy does not work (
Keywords: diabetic neuropathies; blood glucose; blood chemical analysis; surveys and questionnaires; anesthetics, local; nerve block; pain measurement; treatment outcome